SPE International Conference and Exhibition on Formation Damage Control 2018
DOI: 10.2118/189523-ms
|View full text |Cite
|
Sign up to set email alerts
|

Treating Liquid Banking Problem to Increase Shale Gas Wells Productivity

Abstract: One of the common causes of gas wells productivity loss is attributed to liquid accumulation near the wellbore over the production life of the wells. For gas condensate reservoirs, when the bottomhole pressure falls below the dew point pressure, liquid hydrocarbon drops out of the gas phase, residing in the near wellbore region and causing condensate block. Fracturing fluid also contributes to liquid blockage as only 5 to 30% of fracturing fluids are recovered from the reservoir. For a tight shale formation wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Bang et al reported the gas relative permeability could experience up to a 95% reduction due to liquid banking near the wellbore, thereby stopping gas production entirely in many cases . However, the condensate bank formed around the wellbore can be treated using gas injection or surface/interfacial tension reduction or can be delayed by hydraulic fracturing and horizontal completion. Under reservoir conditions, increasing condensate saturation is highly correlated with a reduction in the relative gas permeability in the presence of an immobile liquid . The presence of 19% connate water during condensate formation may decrease the relative permeability of the gas by 60% …”
Section: Introductionmentioning
confidence: 99%
“…Bang et al reported the gas relative permeability could experience up to a 95% reduction due to liquid banking near the wellbore, thereby stopping gas production entirely in many cases . However, the condensate bank formed around the wellbore can be treated using gas injection or surface/interfacial tension reduction or can be delayed by hydraulic fracturing and horizontal completion. Under reservoir conditions, increasing condensate saturation is highly correlated with a reduction in the relative gas permeability in the presence of an immobile liquid . The presence of 19% connate water during condensate formation may decrease the relative permeability of the gas by 60% …”
Section: Introductionmentioning
confidence: 99%
“…They discovered the existence of gas-water two-phase flow, trilinear, and five-linear flow patterns between different flow regions (Bello and Wattenbarger 2010;Brown et al 2009;Ozkan et al 2010;Brohi et al 2011;Ozkanet et al 2011;Stalgorova and Mattar 2012a, b;Yin et al 2015;Zhang et al 2015;Fan and Ettehadtavakkol 2016;Su et al 2016a, b;Zeng et al 2019;Liu et al2020;Behmanesh et al 2021). The flow coupling laws between multiple media were described mathematically by the mass transfer control equation, which considered the typical flow mechanisms such as Knudsen diffusion, molecular surface diffusion, adsorption-desorption, Klinkenberg effect, high-speed non-Darcy effect, Darcy flow, effective stress sensitivity (Carlson and Mercer1991;Wang et al2015;David Obembe et al 2017;Phan et al 2018;Sun et al2019;Zhong and Leung 2019;Hassan et al 2020;Zeng et al 2021). Thereby establishing an analytical model describing the cross-scale transport of shale gas was developed.…”
Section: Introductionmentioning
confidence: 99%